A Case Report of a Malignant Triton Tumor of the Left Retroperitoneum in a Young Female Without Neurofi bromatosis - Dayton Grogan BS; Vamsi Reddy BS; Earl Dane Jones; Cargill H Alleyne (Global Journal of Rare Diseases - Peertechz Publications, 2019)
Malignant peripheral nerve sheath tumors (MPNST) are malignant cancers with origins found within peripheral nerves of various body regions-most commonly involving the buttocks, thighs, brachial plexus and para-spinal region [1]. While MPNSTs account for only 5%-10% of all soft tissue sarcomas, there exist MPNST variations that occur with greater rarity [2]. Specifi cally, Malignant Triton Tumors (MTT) are a subset of MPNST with rhabdomyoblastic differentiation and account for only 5% of all MPNST cases [3]. MTTs were fi rst described by Mason in 1932 and found to occur in patients with Neurofi bromatosis type 1 (NF-1) in slightly more than 50% of cases. This is because sMTTs are believed to originate from Schwann cells of peripheral nerves or within existing neurofi bromas [3,4]. Diagnosis of MTT is confi rmed by immunohistochemical screening for desmin, vimentin, actin, myoglobulin, and S-100 protein.